The Effect of Blood Transfusion on Outcomes in Aortic Surgery - Velasquez, Camilo A.; Singh, Mrinal; Bin Mahmood, Syed Usman; Brownstein, Adam J.; Zafar, Mohammad A.; Saeyeldin, Ayman; Ziganshin, Bulat A.; Elefteriades, John A. (International Journal of Angiology, 2017)
The use of blood transfusion in cardiac surgery varies widely. The beneficial effects of blood products are offset by an increase in morbidity and mortality. Despite multiple studies showing an association between blood product exposure and adverse short- and long-term events, it is difficult to determine causality. Nevertheless, the implication is sufficient to warrant the search for alternative strategies to reduce the use of blood products while providing a standard of care that optimizes postoperative outcomes. Aortic surgery, in particular, is associated with an increased risk of bleeding requiring a blood transfusion. There is a paucity of evidence within aortic surgery regarding the deleterious effects of blood products. Here, we review the current evidence regarding patient outcomes after blood transfusion in cardiac surgery, with special emphasis on aortic surgery.
Keywords: cardiac surgical procedures; thoracic surgery; thoracic aorta; blood transfusion; morbidity; mortality; thoracic aortic aneurysm; dissection